2005
DOI: 10.1017/cbo9780511614613
|View full text |Cite
|
Sign up to set email alerts
|

Reformation and the Culture of Persuasion

Abstract: Why did people choose the Reformation? What was it in the evangelical teaching that excited, moved or persuaded them? Andrew Pettegree here tackles these questions directly by re-examining the reasons that moved millions to this decisive and traumatic break with a shared Christian past. He charts the separation from family, friends, and workmates that adherence to the new faith often entailed and the new solidarities that emerged in their place. He explores the different media of conversion through which the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…For another thing, reading as a communal activity -reading aloud -has remained a significant cultural practice (Boyarin, 1992). In a critique and redevelopment of Eisenstein's (1979) classic study of the role of printing presses and books in the Reformation, Pettegree (2005) showed how both processes of reading and of converting to a new faith were public activities involving singing, preaching, drama, and visual images, as well. Furthermore, readers themselves became writers, adding comments or 'marginalia' (Jackson, 2001), perhaps alongside those of others already appearing in book margins (anticipating user tags in digital media), and taking notes for later inclusion in letters.…”
Section: Media Of Three Degreesmentioning
confidence: 99%
“…For another thing, reading as a communal activity -reading aloud -has remained a significant cultural practice (Boyarin, 1992). In a critique and redevelopment of Eisenstein's (1979) classic study of the role of printing presses and books in the Reformation, Pettegree (2005) showed how both processes of reading and of converting to a new faith were public activities involving singing, preaching, drama, and visual images, as well. Furthermore, readers themselves became writers, adding comments or 'marginalia' (Jackson, 2001), perhaps alongside those of others already appearing in book margins (anticipating user tags in digital media), and taking notes for later inclusion in letters.…”
Section: Media Of Three Degreesmentioning
confidence: 99%
“…58 Taylor, Heresy and orthodoxy, p. 188. 67 In 1567 Chesneau entered in collaboration with Jean Talpin, who, like Benoist, had been granted an authorial privilege and Chesneau produced the near majority of Talpin's vernacular output. this remained a dead letter as the Sorbonne repeatedly petitioned the privy council for the printers to be punished and the Bible to be quashed, all to no avail.…”
Section: N I C O L a S C H E S N E A U C A T H O L I C P R I N T E Rmentioning
confidence: 99%
“…74 It would seem that the Acoleyen was keen to avoid further reprimands in the 1561 festival: hence it instructed its guests not to use the occasion 'to provide an outlet for criticism of orthodox religion'. 75 Regarding the three winning refreins themselves, it is difficult to establish exactly why each took first prize in its particular category. Silvius' volume gives no indication of the criteria used in judging the pieces, and does not single out any of their features as especially praiseworthy.…”
Section: The Texts and Translationmentioning
confidence: 99%